Genetically expressed cameleon in Drosophila melanogaster is used to visualize olfactory information in projection neurons. - Fiala, A.; Spall, T.; Diegelmann, S.; Eisermann, B.; Sachse, S.; Devaud, J.M.; Buchner, E.; Galizia, C.G. (Current Biology, 2002)
Complex external stimuli such as odorants are believed to be internally represented in the brain by spatiotemporal activity patterns of extensive neuronal ensembles. These activity patterns can be recorded by optical imaging techniques. However, optical imaging with conventional fluorescence dyes usually does not allow for resolving the activity of biologically defined groups of neurons. Therefore, specifically targeting reporter molecules to neuron populations of common genetic identity is an important goal. We report the use of the genetically encoded calcium-sensitive fluorescence protein cameleon 2.1 in the Drosophila brain. We visualized odorant-evoked intracellular calcium concentration changes in selectively labeled olfactory projection neurons both postsynaptically in the antennal lobe, the primary olfactory neuropil, and presynaptically in the mushroom body calyx, a structure involved in olfactory learning and memory. As a technical achievement, we show that calcium imaging with a genetically encoded fluorescence probe is feasible in a brain in vivo. This will allow one to combine Drosophila's advanced genetic tools with the physiological analysis of brain function. Moreover, we report for the first time optical imaging recordings in synaptic regions of the Drosophila mushroom body calyx and antennal lobe. This provides an important step for the use of Drosophila as a model system in olfaction.